Pengembangan Sistem Aplikasi Persuratan Elektronik Berbasis Web di Fakultas Ilmu Komputer (FILKOM) Universitas Brawijaya - Habib Trizaka; Denny Sagita Rusdianto; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Letter has become a written communication media that is important to fulfill lots of organizations or companies needs. The current thought about organizing letters is that it needs high level of precision which is take too long to be done. This situation is similar to what happened in Faculty of Computer (FILKOM) University of Brawijaya. They have been using Microsoft Excel to manage all of the corresponding letters until this time. In this way, the distribution of letters has become less effective knowing that there is no integration between units/divisions. Oftentimes, the distributed letter is stopped because of some reasons. It could be that the receiver is not available at that time, or there is no information whether the letter has already been handled or not. These kinds of problems can be solved by developing a web-based letter management system where each unit is integrated to one another. In this way, the distributed letter and its monitoring can be easily done without considering place and time. Waterfall model process is used by the author in developing the software. In requirement engineering phase, there are found 33 functional requirements and 1 non-functional requirements. Based on the requirement engineering result, system is designed to be implemented in the next phases. The testings performed are unit testing, integration testing, and validation testing that result 100% valid in all test scenarios. And based on the compatibility testing, it is known that the system worked with no problems occurred in 73% of 11 versions of tested browsers.